IMPLEMENTASI BUDAYA SEKOLAH DI SD YPS SINGKOLE SOROWAKO - Margono, Handayani (Pascasarjana Universitas Negeri Makassar, 2015)
Primary education is implemented through formal education as in SD (elementary school). SD YPS Singkole is a school that cares about quality improvement which focuses the effectiveness of the implementation of school culture. This is the focus of the study.This Study employed quantutative design with descriptive qualitative. The format is usually used for a case study with the main problem on the description of the effectiveness of the implementation of school culture aspects and the development of school culture strategies as well as the internal and external factors which influence the implementation of school culture. The data were analyzed by employing Miles and Huberman model.The result of the study reveal that (1) the implementation of school culture at SD YPS Singkole in Sorowako based on indicators showed various result. The implementation of the value of achievement is categorized as fair, the value of honesty is categorized as fair, the value of discipline is categorized as good, the value of hygiene is categorized as poor, family value is categorized as good, the value of togetherness is categorized as fair, and the value of appreciation is categorized as fair: (2) the development of school culture strategies which support the implementation of the value of school culture among others are the involvement of parents, sense of school, and building relation aligned with the development of the implementation of the value of achievement, building trust aligned with the development of the implementation of the value of honesty. Safety assurence aligned with the development of the implementation of the value of togetherness, positive motivation aligned with the development of the implementation of the value of appreciation, sense of school and the connection with the development of the implementation of the value discipline, buliding relation aligned with the development of the implementation of the value of hygiene, and the leadership of principal aligned with the development of the implementation of family values: (3) the internal factor which influence the implementation of school culture in term of strenght is basically from the support from the foundation, which are the facility and infrastructure, high commitment from the teacher , and strict discipline; whereas the internal factor in term of the weakness in implementing school culture is lack of understanding on school culture from the teachers; (4) the external factor which influence the school culture in terms of opportunity as well as the challenge which influence the implementation of school culture at SD YPS Singkole is dominantly from the parents and the people.